Impacts of Urban Traffic and Transport on Social Determinants of Health from the Perspective of Residents and Key Informants in Sanandaj, Iran: A Qualitative Study - Haidar Nadrian; Mohammad Hossein Taghdisi; Davoud Shojaeizadeh; Saharnaz Nedjat (Journal of Education and Community Health)
Background and Objective: Traffic and transport, as a political and social phenomenon, play an important role in the quality and socioeconomic structure of a society. This phenomenon constitutes one of the foundations of modern urban life and social needs of populations. Regarding this, the present study was performed to investigate the impacts of urban traffic and transport on the social determinants of health (SDH) based on the viewpoints of urban residents and key informants in Sanandaj, Iran. Materials and Methods: This qualitative study was conducted on 22 urban residents and 8 key informants selected through purposive sampling technique. The data were analyzed through conventional content analysis approach. Data collection was conducted using four focus group discussions (FGDs) (including 22 residents) and eight in-depth interviews. MAXQDA10 was applied for the purpose of data management. Results: The SDHs that were negatively affected by Sanandaj urban traffic and transport included socio-cultural (e.g., recreation and free times, daily work trends, safety of within-city commuting, tobacco use, and education) and environmental factors (e.g., vegetation, antiquities, noise pollution, urban aesthetic status, and environment, and soil, food, and water status). Conclusion: Urban traffic/transport stakeholders, health policy makers, and health professionals in Iran should pay much more attention to the impacts of urban traffic/transport plans on health and its determinants. It seems necessary to comprehensively assess urban traffic/transport on health status and its determinants in Iran.